Addiction to Social Networks and Social Skills in Students from a Private Educational Institution - Domínguez Vergara, Julio A. (2016)
This research aims to determine the relationship between addiction to social networks and social skills in students of a private educational centre. A correlational descriptive study where the sample was represented by 205 students from 1st to 5th grade of junior high school was conducted. Two instruments were used: “Goldstein Social Skills Checklist” and “Scale of Attitudes toward Social Networks”, this was adapted and validated for the population. It is concluded that addiction to social networks of the Internet has a significant relationship (p <.01) with social skills, indicating that the greater the addiction to social networks is, a low level of social skills in adolescents is perceived.